(untitled) (JULACE: Journal of the University of Namibia Language Centre, 2022)
Despite the efforts done by the Tanzanian Government regarding gender equality and human rights in a bid to enhance poverty eradication strategies, the Kuria culture presents major obstacles to the endeavours by holding back the development efforts initiated by Kuria women. This obvious gender inequality manifests itself not only in socio-cultural practices but also in the language used to refer to women and men. This article examines language, gender and culture in relation to Kuria women in Kuria society. The article aimed to examine the power behind the language of Kuria male to female, the effort done by the Kuria women for sustained development and the measures to be taken by the Government. The data for this article were collected through interviews, focus group discussions and different current sources of relevant literature published at least after 2000s. This article is anchored on the theory of Gender Practices. The findings have revealed that language, gender and culture are interconnected and cannot be separated. Language is not simply the reproducing tool for the expression of thoughts but rather, is itself the shaper of thought/ideas, the platform and guide for the individual’s mental action, for scrutiny of impressions.